Preparation and characterization of BSA-loaded Chitosan Microspheres - Esti Hendradi; Retno Sari; Rifka Anggraini Anggai (Health Notions, 2018)
Proteins are unstable molecules because of their complex structure and easily degraded by enzymatic systems. Biodegradable microspheres have been used in protein delivery system. Bovine serum albumin was chosen as a model protein. Chitosan/tripolyphosphate microparticles have already been used to encapsulated BSA. The aim of this work was to microencapsulate these protein-CS/TPP by ionic gelation and freeze-drying. The morphology, particle size, and encapsulation efficiency of the prepared microspheres were investigated. The results revealed that the microspheres exhibited good sphericity with ranged in size from 2.25 to 2.73 µm. The study found that the moisture content of microspheres was 2.8%, the encapsulation efficiency of BSA in CS-TPP microspheres ranged from 88.14 to 96.25%. The results suggested that iontoropic gelation method will be an effective method for fabricating chitosan microspheres for delivery of protein.. Keywords: Microspheres, BSA, Ionic Gelation